Pengembangan Media Pembelajaran Papan Kata pada Pembelajaran Fabel Siswa Kelas VII Sekolah Menengah Pertama Negeri 1 Tanjungpinang: Pengembangan media pembelajaran papan kata pada pembelajaran fabel siswa kelas VII sekolah menengah pertama Negeri 1 Tanjungpinang - Pika Miranti; Abdul Malik; Ahada Wahyusari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research aims to develop word board learning media for class VII students at Tanjungpinang 1 State Junior High School for the 2022/2023 academic year by reviewing the level of validity and practicality of the use of the media being developed. The development model used in this research is the 4D model which starts from the define stage. design (design), develop (development). The media that researchers developed in this research is creative visual learning media in the form of a fable material word board with several questions that must be completed to see students' abilities in understanding fable material. The word board was media validated by two experts, namely a material expert and a media expert. The number of students in the group for testing the practicality of learning media was 5 students for the small group and 35 students for the large group. Data collection techniques in this research used interviews, media validity questionnaires, and media practicality questionnaires. The data analysis techniques in this research are quantitative descriptive to analyze the scores for assessing the validity and practicality of the media and qualitative descriptive to analyze comments, suggestions and input on the media. The results of this research are word board learning media with a validation percentage from material experts reaching 95% with the qualification